Effect of water salinity stress on dates biometric and biochemical characteristics - krid, keltoum (Algerian Journal of Biosciences, 2022)
The problem of salinity of irrigation water in palm groves has led us to conduct this study based on the comparison of the quality of dates Deglet Nour and Ghars from two farming systems in the region of El-Oued according to the EC irrigation water. Salt stress in El'Ghout causes in both varieties a regression of biometric characteristics, pH, EC, water content and dry matter, while total sugars are high. The dates of the farm are more voluminous, less acidic, with high ash content, dry matter and high electrical conductivity. According to standards Algerian of date classification reveals that the characteristics of Deglet Nour dates of El'Ghout are more damaged by the salinity of the environment. The two varieties of the farm have better characteristics than those of El'Ghout. It also appears that the salinity of water improves the sugar content of dates